Pengaruh Kampanye Gerakan 3M Terhadap Perubahan Sikap Masyarakat (Studi Kasus Kecamatan Koja, Jakarta Utara) - Zsazsa Saskia Aryani; Santi Delliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Thats study aims to identify the level of public awareness in the Koja Subdistrict area, North Jakarta regarding the dangers of the Covid-19 virus and how influential the 3M campaign has been on changes in people's attitudes in the Koja District area, and to find out the application of the transtheoretical model developed by Prochaska & Diclemente. Researchers used the Positivism Paradigm, using a quantitative approach and the type of research used in this study was descriptive. This research will be conducted in the community area of ​​Koja District, North Jakarta. The reason the researchers chose this location was because the people of the Koja sub-district in North Jakarta still violated the rules set by the government, the positive rate of Covid-19 was still very high compared to other regions. When this research was conducted in October to November 2020. Primary data was obtained from the results. Observation by means of direct observation and recording of respondent's knowledge and comparisons of data using research instruments (questionnaires). Based on the results of the research, the Validity Test of variable X has a data value of 0.722 for r count the first question and data 0.876 for r count to question 20 with r table 0.254. variable Y for the first question and 0.442 for the 10th question data with r table 0.254.